Keragaman Bacaan Qunut Di Kalangan Ulama Salafi, Al-Jam'iyatul Washliyah, Nahdhatul Ulama, Dan Muhammadiyah - Natasya Ammar; Eny Nazrah Pulungan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The issue of furu'iyah in the Islamic religion is indeed a very interesting study if we look closely, so sometimes it becomes a striking difference if it is understood one-sidedly, moreover it becomes an arena for endless debate so that sometimes we find groups that are not in line, claiming they do not follow the rules of the Islamic religion as a whole. Correct. Things like this should be straightened out by re-examining the correct legal basis so that those who practice it feel more confident in practicing it, as well as those who don't practice it and don't claim to be heretical or heretical to other groups. Likewise with the implementation of the Qunut prayer in prayer, there are differences within the Muslim community, there are some groups who perform it and also leave it out of the prayer sequence where it is sunnah to recite it. This does not happen without reason considering that there is a lot of Islamic literature that is used as a reference by each group which is indeed different from one group to another, whereas the differences in Islam as long as they do not go outside the corridors of sharia, let alone aqidah, are a blessing for the Islamic ummah itself.